Jugoslávie, Srbsko, Kosovo : kosovská otázka ve 20. století - Štěpánek, Václav (Spisy Masarykovy univerzity v Brně, Filozofická fakulta, 2011)
Kosovo issue represents a comprehensive complex of problems and issues, ensuing from troubles involving the coexistence of provincial Albanian majority and Serbian minority, residing at small common territory situated in the middle of Balkans. The submitted monograph describing the Kosovo issue covers the entire 20th century. Wherever it may be necessary, we strive to disclose deeper roots of some phenomena, or in cases, where an interpretation of certain development trends may remain unclear without elucidating their historical past. It specifies trials of Yugoslavian establishment to resolve.